INTERIM REPORT OF THE STANDARDS RATING COMMITTEE. - Miller, Hermann C. (The Accounting Review, 1951)
Abstract The Standards Rating Committee was appointed in 1949 for a period of five years upon authorization of The Executive Committee, meeting in Columbus, Ohio in May 1948. This committee continued the work of similar committees appointed and serving during the calendar years 1947 and 1948. A portion of the program of study by the committee has now been tentatively completed. This report is therefore submitted with the hope that it will be given full publicity to the members of this Association and generally to all interested persons. The primary objectives of the Committee were agreed upon at the first meeting. These objectives may be suggested by the needs expressed in the following statements adopted unanimously by the Committee. The Committee has therefore attempted to bring out a suggested program of acceptable standards. It is important that proposals herein be accepted generally and put into effect as quickly as feasible in the framework of educational institutional procedure or that objections, criticisms and suggestions be made for the purpose of restatement and revision.